Effectiveness of HDTMA-Br Surfactant Modified Jackfruit Peel Activated Carbon Adsorption on Methylene Blue - Nabillah, Ghoiriah; Dewi, Ratna Sari (Indonesian Journal of Chemical Science and Technology (IJCST), 2024)
Jackfruit peels are usually considered as waste and cause environmental pollution. However, banana peels can be used as an adsorbent material to reduce the impact of methylene blue dye use because they contain high lignocellulose. This study aims to determine the characterization, optimum mass and optimum time. Adsorbents are made using dried and carbonized jackfruit skin at a temperature of 400°C for 2 hours. After the carbonization process, the adsorbent was activated using 5 M potassium hydroxide for 4 hours. . Based on the research results, it shows that the optimum mass of carbon is found at a mass of 0.16 grams and the optimum mass for activated carbon and HDTMA Br activated carbon occurs at a mass of 0.07 grams. Meanwhile, the optimum time for carbon was 60 minutes and for activated carbon and HDTMA Br activated carbon was 45 minutes.